Pygmodispus (Pygmodispus) paraequestris spec. nov. (Acari: Heterostigmata: Scutacaridae) from Turkmenistan - Khaustov, Alexander A.; Chydyrov, Peyzulla R. (Zootaxa, 2003)
Pygmodispus (Pygmodispus) paraequestris spec. nov. (Acari: Scutacaridae) is described from the soil of a cotton field from Turkmenistan. The new species is very closely related to P. equestris Paoli, 1911, but differs from it by a much more massive claw on tibiotarsus I, by a more massive process of trochanter IV and by a shorter solenidion w2 on tibiotarsus I.